Pengaruh Sanksi Pajak dan Kesadaran Wajib Pajak pada Kepatuhan Wajib Pajak - Putra Pranata, I Gusti Bagus; Jati, I Ketut (E-Jurnal Akuntansi, 2019)
The purpose of this study was to determine the effect of tax sanctions and taxpayer awareness on corporate taxpayer compliance. The study was conducted at the Gianyar Pratama Tax Service Office. The number of samples taken as many as 100 corporate taxpayers, by convenience sampling method. Convenience sampling method is sampling taken randomly by considering the ease of access that can be reached by researchers. The analysis technique used is multiple linear regression. The results of the study mean that the higher the tax sanction, the higher the level of taxpayer compliance, and vice versa. Based on the results of this study the awareness of taxpayers has a positive effect on taxpayer compliance so that the second hypothesis in this study is accepted. Keywords : Taxes; Taxpayers; Sanctions; Awareness; Compliance.